Value Engineering Study on Drainage Channel Works on AW. Syahranie Road, Samarinda - Sundari, Sundari; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2025)
Flooding on roads still often occurs in several cities, especially densely populated cities. If the problem of flooding is not resolved, it can cause a bigger disaster that harms the local community, both property and lives. Jalan Aw. Syahranie Samarinda is one of the roads in Samarinda City that still often experiences flooding due to drainage channels that cannot accommodate or drain surface water. The purpose of this study is to analyze the application of Value Engineering in the Construction of the Jalan Aw. Syahranie Samarinda Drainage Channel. The solution method in this calculation uses Value Engineering Analysis. Value Engineering Analysis is carried out when the Budget Plan (RAB) is still being planned to get maximum results. This research method is carried out with five stages of Value Engineering, namely the information stage, the function analysis stage, the creative stage, the evaluation stage and the presentation stage. The weight of each criterion uses the Zero-One Method. Zero-One Analysis Matrix Method The use of the zero-one method is carried out for weighting and assigning values ??to the criteria. From the analysis results obtained that the best alternative that can replace the initial implementation method on selected work items in concrete work is Ready Mix Concrete and Conventional Concrete using a mixer. The cost savings obtained are Concrete Work with the first alternative choice, namely Conventional Concrete using a mixer, has the highest weight with a ranking of 1 and a savings value of 9.86% or Rp 397,393,488. The total overall savings for the work in VE with the overall cost of the project for the initial plan is Rp. 16,751,587,077 while the overall cost of the project after Value Engineering is Rp 16,354,193,589. With the cost saved being Rp 397,393,487.76 or 2.75% of the total project.